Organizational cronyism and employee psychological withdrawal behavior: the mediating role of disidentification and moderating effect of employability - Chunning Xu; Sadia Shaheen; Muhammad Waseem Bari (BMC Psychology)
Abstract Grounded in the conservation of the resource theory, this study aims to investigate the impact of organizational cronyism on the psychological withdrawal behavior of employees with the mediating role of organizational disidentification and moderating role of employability. Data were collected in two-time waves from 267 IT employees. The study’s findings revealed organizational cronyism increases psychological withdrawal behavior through organizational disidentification. Moreover, employability reduces the negative impact of organizational cronyism on organizational disidentification. This study contributes to the literature on organizational cronyism by highlighting the mediating role of organizational disidentification and the moderating role of employability. The study concludes by highlighting the conclusion, managerial and theoretical implications along with limitations and future research directions.